Pengaruh Motivasi, Konflik dan Stress Kerja terhadap Kinerja Karyawan PDAM Tirto Negoro Sragen - Marcella Palupi Untiasari; Asih Handayani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The study aims at studying the significance of motivation, conflict, and work stress influence on the performance of PDAM Tirto Negoro Sragen. The sources of data used in this study are primary data and secondary data. The sample used in this study consisted of 103 PDAM Tirto Negoro Sragen. Sampling techniques use proportional cluster random sampling. Data collection techniques used are questionnaires, observations and library studies. Data analysis techniques use descriptive analysis, double linear regression test, t test, F test, and determination coefficient test. The results show that motivation, conflict and work stress influence the performance of PDAM Tirto Negoro Sragen.